Social cognition in first episode adolescent depression and its correlation with clinical features and quality of life. (January 2021) - Tekin, Uğur; Erermiş, Hatice Serpil; Satar, Ayşegül; Aydın, Ayşe Nur; Köse, Sezen; Bildik, Tezan
Research has suggested that patients with depression have deficits in social cognition, however they provide limited data regarding adolescent depression. Moreover, the relationship of social cognition with clinical features and quality of life is less studied. This study investigated social cognition in depressive adolescents and the correlations of social cognition with clinical features and quality of life. Thirty-five depressed adolescents and 37 healthy controls were assessed. Emotion perception and decoding ToM, quality of life and clinical variables were evaluated. No significant differences were found between depression and control groups regarding social cognitive tests. The results indicated that examined clinical features were not correlated significantly with social cognitive tests. Results suggest that social cognitive abilities are not disturbed in adolescents with first depressive episode.